The Shakespeare apocrypha and canonical expansion in the marketplace - Kirwan, Peter (University of Iowa, College of Liberal Arts & Scirences, 2012)
An essay is presented on the marketing of William Shakespeare's literary works. It offers a discussion on the process of canonization and examines the theatrical production "Double Falsehood," by Lewis Theobald. The author also reflects on the critical reassessment of Lukas Erne on Shakespeare's popularity in more than 45 editions between 1584-1616.